About a rare cause of a coxitis. Issue 1 (8th December 2019) - Kaffel, Dhia; Triki, Wafa; Maatallah, Kaouther; Ferjani, Hanene; Riahi, Hend; Jlalia, Zied; Hamdi, Wafa
Abstract: OO of the acetabulum can clinically and radiologically mimic an ankylosing spondylitis (with coxitis and sacroiliitis). Management of OO include multidisciplinary approach including radiologist, rheumatologist, and orthopedist. Abstract : OO of the acetabulum can clinically and radiologically mimic an ankylosing spondylitis (with coxitis and sacroiliitis). Management of OO include multidisciplinary approach including radiologist, rheumatologist, and orthopedist.